Network of attention to women in the situation of domestic violence under the opinion of the nurse (Research, Society and Development, 2020)
Objective: to ascertain the nurses' understanding of the Family Health Strategy about the care network for women in situations of domestic violence. Method: qualitative, descriptive-exploratory study, conducted with eight nurses from Family Health Units. The semi-structured interview was used to collect data and to analyze the content analysis technique. Results: nurses' lack of knowledge about the existence of the network, limited preparation to deal with domestic violence against women and lack of articulation of services seen as obstacles in solving the problem of domestic violence against women. Conclusion: rethinking the articulation of the care network for women in situations of violence and nurses who work at the gateway with users, also the need to build spaces for dialogue with professionals, services and the population, in order to strengthen services for the networking, with a view to comprehensive care for women in situations of violence.